1994
DOI: 10.1143/jjap.33.7037
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Etching Using Surface Wave Coupled Plasma

Abstract: The EPR spectra of RbMgBr3 crystals doped with Mn2', CP' and Gd3' indicate that the host lattice undergoes two structural phase transitions between the melting point and 77 K. At high temperatures, 738-449 K, RbMgBr3 adopts the hexagonal CsNiCls structure which consists of identical symmetric [MgBr?], chains (phase I). At intermediate temperatures, 44P-235 K, the structure appears to contain two structurally distinct types of [MgBr?], chains (phase 11). The spectral properties indicate that one type of chain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…In particular, it has been recently revealed that inductively coupled ͑IC͒ and surface wave sustained ͑SWS͒ plasmas produced in C 4 F 8 ϩAr gas mixtures have an outstanding potential for ultra-fine and highly selective etching of large-area polysilicon wafers. 2,3 Physically, it appears possible to achieve high dissociation rates of the feedstock gas and densities (ϳ10 13 cm Ϫ3 ) of neutral radicals at low ͑ϳ20 mTorr͒ pressures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been recently revealed that inductively coupled ͑IC͒ and surface wave sustained ͑SWS͒ plasmas produced in C 4 F 8 ϩAr gas mixtures have an outstanding potential for ultra-fine and highly selective etching of large-area polysilicon wafers. 2,3 Physically, it appears possible to achieve high dissociation rates of the feedstock gas and densities (ϳ10 13 cm Ϫ3 ) of neutral radicals at low ͑ϳ20 mTorr͒ pressures.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In this article, we consider the charging of micron-size particulates in fluorocarbon plasmas frequently used for ultrafine, highly efficient, and selective etching of dielectric materials. 11,12 We demonstrate that in plasmas of fluorocarbon-argon gas mixtures, used in etching experiments, 13 molecular ions CF ϩ , CF 2 ϩ , and CF 3 ϩ significantly contribute to the particulate charging and charge relaxation process. We also improve the conventional charging model by accounting for the variations of background electron number density, which inevitably accompanies the particle charge variation.…”
Section: Introductionmentioning
confidence: 86%
“…[11][12][13][14] Due to the overwhelming complexity of fluorocarbon-argon plasmas, the actual composition of the ions and radicals depends on many factors, including the kind of plasma source, the way power is coupled to the plasma, operating pressure, and gas inlet ͑proportions of C 4 F 8 and Ar͒. In the process of etching, molecular species C 4 F 8 almost completely dissociate into smaller ionic ͑superscript ''ϩ''͒ and radical ͑superscript ''0''͒ fragments, such as CF 3 ͑0,ϩ͒ , CF 2 ͑0,ϩ͒ , CF…”
Section: Formulationmentioning
confidence: 99%
“…These problems are well addressed by using surfacewave plasma sources [7][8][9][10] based on slot antennas [4][5][6] (in what follows, we will refer to these simply as slot-antenna plasma sources). When these sources are used, it is possible to generate a downstream plasma [11] at the moderate pressures (2 to 200 Pa) that are most suitable for chemical reactions without having to discharge the substrate side with microwaves.…”
Section: Introductionmentioning
confidence: 99%